Visual Outcome of Cataract Surgery after Phacoemulsification - Rafiq Muhammad, Syed Akhtar, Sanaullah, Muhammad Saim Khan, Bilal Murtaza (Pakistan Journal of Ophthalmology, 2017)
Purpose: To observe the effect of phacoemulsification cataract surgery on visual acuity as well as record the frequency of complications associated with this procedure. Study design: Observational study Place and duration of study: The study was conducted at Khalifa Gul Nawaz Teaching Hospital (KGNTH), Bannu, Pakistan from Jan 2014 to Dec 2016. Material and methods: Patients who had significant senile cataract affecting quality of life were included in the study. Patients suffering from congenital, traumatic, secondary cataract amblyopia, corneal opacity, uncontrolled glaucoma, uncontrolled diabetes, severe diabetic retinopathy, diabetic macular edema or other retinal diseases were also excluded. Ethical approval was obtained from ethical review board of Army field hospital, KhalifaGul Nawaz Teaching Hospital (KGNTH), Bannu. All the included patients were registered the preoperative unaided visual acuity (UCVA), best corrected visual acuity (BCVA were noted. Detailed slit lamp examination including both anterior and posterior segments was carried out. Patients were reviewed on day 1, 14 and then at 01 month. Postoperative UCVA and BCVA were noted at 04 weeks. Results: A total of 1061 eyes of 772patients suffering from senile cataract were included in the study. Mean age of patients was 63.77 + 5.27 years, 56% (594)of the patients were females while 44 % (467)were males. All the surgeries were performed under local anesthesia. 54% (622) of the eyes were right while 46% (439) were left. Good final visual outcome was seen in 80.5% of the cases. Intraoperative complications occurred in 5.4% (60) eyes of patients and posterior capsular rupture seen in 3.01 % (32) Conclusion: Phacoemulsification is safe and effective procedure with good visual outcome if performed in experienced hands under meticulous disinfection and aseptic measures. Keywords: Phacoemulsification, Cataract surgery, Visual outcome, Posterior capsular rupture